Understanding the Influence of Family Dynamics on Gender Identity Formation in Pre-school Children - Briella, Theodora Anggika (Acta Psychologia, 2024)
Gender identity development in pre-school children is a complex process influenced by individual, familial, and societal factors. This research investigates the role of the family in shaping children's understanding and expression of gender, drawing on a mixed-methods approach that combines qualitative interviews, observations, and quantitative surveys. The study examines parental socialization practices, attitudes, and beliefs regarding gender, as well as the influence of sibling and peer interactions, cultural norms, and socioeconomic factors within the family context. Findings highlight the central role of parents as primary socialization agents, transmitting cultural norms and values related to gender through everyday interactions and practices. Sibling and peer influences further shape children's understanding of gender, while cultural and societal factors intersect with family dynamics to influence perceptions of gender roles and expectations. Practical implications for parents, educators, and policymakers are discussed, emphasizing the importance of fostering awareness, reflection, and action to create supportive environments that empower children to explore and embrace their gender identity authentically and affirmatively. Overall, this research contributes to a deeper understanding of the processes underlying gender identity formation in early childhood and informs interventions and policies aimed at promoting healthy gender development in pre-school children.